Early seventeenth century Tagalog : lexical morphological and syntactic features - Madrigal, Vida Maria C. (Animo Repository, 1988)
This study demonstrates that the Tagalog language has, in time and space, manifested a considerable degree of utility and creativity in its vocabulary. Likewise, it sets to show the quality and quantity of differentiation in meaning of the language throughout the last 300 years.The study discussed the historical, biographical, and textual aspects of the materials. The different lexical, morphological and syntactic features were compared and contrasted within two historical periods, the early 17th and the late 20th centuries. The investigated linguistic materials were extracted from the two earliest extant published books in the Philippines about the Tagalog language: the Arte y reglas de la lengua Tagala, 1610, of Blancas de San Joseph, O.P. and the Vocabulario de la lengua Tagala, 1613, of Pedro de San Buenventura , O.S.F. The forms of change undergone by the Tagalog language is shown in the following statistical information: number of items demonstrating lexical changes: 1,476 number of types demonstrating morphological changes: 76 number of types demonstrating syntactic changes: 145. Throughout the presentation of the different linguistic items, the study resorted to contrasting, exemplifying, and whenever necessary and possible, explaining the characteristic behavior of change of Tagalog. Firstly, the inquiry disclosed that the bulk of differentiation facets of old Tagalog culture are mirrored in ancient phraseologies and metaphorical expressions that have gone out of use and distinctly observable from obsolete items and archaic idiomatic expressions.The second type of change that seemed significant was the process whereby linguistic items exhibiting the same form of demonstrated semantic change. In the morphological level, the most detected type of change centered on the process of Simplification. It seemed to dominate specially the changing patterns of the Tagalog pronoun and adjective. On syntactic changes, the most common pattern of modification affected the verb phrase.The study concluded with discussions on the trend of change, observed from the different types of change demonstrated in the entire study, that should serve as a summarized index on how, where (linguistic levels), and to what extent the Tagalog language has evolved throughout the last 300 years. No reasons as attempted for the 'cause' of change, except for those rationalizations that parallel the authorities' arguments on the conditions surrounding the factors of change. In showing that Tagalog Lexicon both in word and phrasal level, has been demonstrating semantic tractability and creativity, and in presenting Tagalog Morphology and Syntax as having exhibited gammatical flexibility, the study, in effect, have been describing their earlier gradations of standardization.